2016
DOI: 10.1111/bjd.14718
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasin (S100A7) promotes stress-induced angiogenesis

Abstract: SummaryBackground Vascular modifications occur early in the development of psoriasis, and angiogenesis is one of the key features in the pathogenesis of the disease. Objectives To identify the role of the S100 protein psoriasin in psoriasis-associated angiogenesis. Methods The role of psoriasin in mediating angiogenesis was investigated by silencing psoriasin with small interfering RNA (siRNA) and measuring psoriasisassociated angiogenic factors in human epidermal keratinocytes. The secretion of psoriasin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 44 publications
0
35
0
2
Order By: Relevance
“…Elevated expression of psoriasin in psoriatic plaques (Morizane and Gallo, 2012), as well as in other hyper-angiogenic conditions, has validated it as a marker to assess in the context of psoriasis (Vegfors et al, 2016). Additionally, psoriasin is a chemotactic for CD4+ T cells and neutrophils (Jinquan et al, 1996), and is induced by psoriasis-associated inflammatory cytokines that include IL-1β, IL-17, IL-22, and TNF-α (Liang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression of psoriasin in psoriatic plaques (Morizane and Gallo, 2012), as well as in other hyper-angiogenic conditions, has validated it as a marker to assess in the context of psoriasis (Vegfors et al, 2016). Additionally, psoriasin is a chemotactic for CD4+ T cells and neutrophils (Jinquan et al, 1996), and is induced by psoriasis-associated inflammatory cytokines that include IL-1β, IL-17, IL-22, and TNF-α (Liang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the BJD , Vegfors et al . found that stress signals, such as hypoxia and reactive oxygen species (ROS) induce S100A7 expression in keratinocytes.…”
mentioning
confidence: 99%
“…Vegfors et al . also showed that hypoxia and ROS can increase the expression of S100A7 in keratinocytes, but it is not clear how a hypoxic and inflammatory microenvironment induces angiogenesis.…”
mentioning
confidence: 99%
“…CCL20, CCL27 and monokine induced by γ-interferon (MIG) participate in involvement of T-cells to the psoriatic rash zone [14,15,21]. Moreover, in psoriasis the release of angiogenic factors and pro-inflammatory cytokines intensifies, and the level of anti-inflammatory cytokines decreases [9,22].…”
Section: And 10 Th Days Of the Treatment The Progressive Improvement mentioning
confidence: 99%